IRINGAN ORGANIS DAN PENGHAYATAN IMAN UMAT DALAM PERAYAAN EKARISTI - Chiaralazzo, Monica Innanda; Tarihoran, Emmeria; Darianto, Darianto (Bahasa Indonesia, 2024)
This study aims to demonstrate the significance of the organist's role in enhancing the faith experience of the congregation during the celebration of the Eucharist. The research was conducted at the Church of St. John the Baptist in Malang using a quantitative approach. Data collection used a research instrument in the form of a questionnaire whose validity had been tested using Aiken's V and was declared reliable based on the Alpha Cronbach formula. Data collection techniques are carried out by utilizing the Google Form. The research respondents were 307 Catholics. Data were analyzed using product-moment correlation (Pearson). The results showed that there was a relationship between organ music accompaniment and the appreciation of the parishioners at the Eucharistic celebration with Pearson's correlation coefficient (0.159) > r table (0.113), meaning that H0, was rejected and H1, was accepted. The Pearson correlation coefficient value is 0.159 when compared to the Pearson correlation criteria guideline table, indicating a fragile correlation level.